Three In One : Character Building And Academic Achievement With The Making Of Game Religion Multimedia Vocational School - Suhada, H. (Universitas Malikussaleh, 2019)
Cases of student brawling, pornography to drug use by students are still concern today. Meanwhile, concerns about the quality of education in our country are increasing because the influence of technology is growing rapidly but it is not being used to the fullest for learning needs. Therefore we need solutions to improve the quality of learning by using information technology. Vocational high school multimedia study program offers the solution of culturally charged religious games, religious education and expertise. Making this religion game was directed by a multimedia productive teacher assisted by both religious and Indonesian Language teacher because the production of religious video game is the result of combining religion, narration and video game making skills. Video game religion can begin with an observation of social and religious life in schools or homes. Literacy can be done to help giving new ideas and value to character, morals and religion. Through the manufacture of religion games, it is expected that students interchange every existing role while learning religion. In addition to video games production can enhance students skills and accomplishments in multimedia majors. The study set out to describe the creation of a game of religion that features the values of character education and Indonesian Language education in multimedia skills programs and make an attractive learning model